Mental Health Analysis of Online Gambling Addicts in Percut Village, Percut Sei Tuan District, Deli Serdang Regency - Santia Putri Khairuna; Syawaluddin Nasution (Journal of General Education and Humanities, 2025)
This study aims to explore the impact of online gambling addiction on individual mental health, especially in Percut Village, Percut Sei Tuan District, Deli Serdang Regency. Using a descriptive qualitative approach and case study method, this study selected five participants from Percut Village who had experience of online gambling addiction to analyze in depth its impact on their mental health. The findings of this study indicate that online gambling addicts experience various mental health problems, including stress, depression, excessive anxiety, sleep disorders, and even thoughts of ending their lives. This study indicates that online gambling not only has an impact on individuals personally, but also has wider negative effects. With the increase in online gambling through technological advances, this study emphasizes the importance of a deeper understanding of the factors that trigger addiction and its impact on mental health.